A review of regenerative medicine and tissue engineering with a focus on wound healing and anti-aging - Ganesan, Ovya; Kiwanuka, Harriet; Hamaguchi, Ryoko; Orgill, Dennis P. (Frontiers in Surgery, 2025)
Regenerative medicine and tissue engineering explore the potential to enhance human healing, which is often limited by wound contraction, scarring, loss of function, and decreased quality of life. Biomaterials like synthetic scaffolds and implantable devices have been developed to circumvent the body's limited natural ability to heal, however, they may introduce their own complications such as toxic side effects. Advances in cell-based therapies, especially those involving embryonic stem cells (ESCs) and human-induced pluripotent stem cells (hiPSCs), offer an enhanced ability to regenerate, circumventing limitations of biomaterials and the body's limited ability to heal. There have been many recent advances in cell-therapies, both scaffold-based and scaffold-free products. Additionally, non-cell-based therapies are gaining traction in wound healing. These products, utilizing their ability to affect the principles of wound healing, have applications in anti-aging. Despite these advances, significant challenges remain. These technologies remain costly, may compromise ethical tenets, and may introduce safety risks. Future work should address these challenges.